2006
DOI: 10.1002/ijc.21646
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization analysis on male breast cancer

Abstract: The spectrum of genetic alterations in primary male breast cancer is not well established. We analyzed chromosomal imbalances in 39 tumor samples from primary male breast cancer by comparative genomic hybridization (CGH) and correlated CGH findings with clinicopathological factors. Chromosomal gains were most frequent at 1q (46%), 8q (46%), 16p (36%), 17q (36%), Xq (28%), 20q (26%) and Xp (18%). Losses were most commonly observed at 8p (36%), 16q (28%), 13q (28%), 6q (18%), 11q (18%) and 22q (18%). Gains at 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
4
13
0
1
Order By: Relevance
“…MBC alterations targeted chromosomes 1, 2, 4, 7, 11, 14 and X in more than 50% of the cases, while chromosomes 1, 2, 3, 7, 11, 15, 16, 17 and 20 were altered in more than 50% of the female series. Our data strengthens the reports of Rudlowski et al [21], who found similar imbalances between male and female BC with a less sensitive CGH. CNAs have been demonstrated to determine cancer predisposition in most high risk cancer syndromes.…”
Section: Discussionsupporting
confidence: 93%
“…MBC alterations targeted chromosomes 1, 2, 4, 7, 11, 14 and X in more than 50% of the cases, while chromosomes 1, 2, 3, 7, 11, 15, 16, 17 and 20 were altered in more than 50% of the female series. Our data strengthens the reports of Rudlowski et al [21], who found similar imbalances between male and female BC with a less sensitive CGH. CNAs have been demonstrated to determine cancer predisposition in most high risk cancer syndromes.…”
Section: Discussionsupporting
confidence: 93%
“…We show here that male and female breast cancers share many similarities and that the main genomic aberrations are indeed the same [41][42][43], despite substantial differences in, e.g., hormonal levels [44] and HER2 status [8]. These results are in line with earlier findings using lower resolution metaphase CGH [43,45], and also imply that the key genes/genomic regions involved in the evolution and progression of MBC might indeed be fairly similar to FBC. Overall, the frequency of genomic aberrations was similar in male and female breast cancers, but when gains and losses were analyzed separately significant differences became apparent, with MBCs harboring more gains and fewer losses than FBCs.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in male breast cancer used the comparative genomic hybridization method to analyze genetic alterations. 7,8 Largely in line with these two studies, we found similarities but also differences in cytogenetic aberrations between female breast cancer and male breast cancer. In the study conducted by Rudlowski et al, 8 gain on 16p and loss of 16q was reported in a lower percentage of cases compared with our results; 36% and 42% vs 31% and 53%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…High-grade ductal cancer often has complex changes, typically small regions of gain together with larger regions of loss. [2][3][4][5][6] Genetic alterations on chromosome 16 in male breast cancer are poorly characterized compared with female breast cancer, and only a few studies have been performed 1,7,8 of which the first analyzes only one gene on 16q and the latter studies analyze small series of male breast cancer. These studies report frequent chromosomal imbalances on both the short and long arm of chromosome 16.…”
mentioning
confidence: 99%